Health literacy mediation in online medical consultations: Advancing inclusion and expanding access to digital healthcare - Zhengpeng Luo (罗正鹏) (Discourse & Communication, 2026)
This paper explores health literacy mediation in Chinese online medical consultations (OMCs). Adopting a social practice view of (health) literacy, the study examines naturally occurring instances of health literacy mediation in which caregivers act as “mediators” by initiating and receiving online medical services on behalf of their family members who may have limited health literacy. The analysis focuses on the discursive and interactional strategies through which these mediators participate in OMCs, articulate their family members’ illness experiences, and support the management of their health. The findings show that literacy mediation serves as a powerful means of addressing health literacy barriers, promoting inclusion, and empowering linguistically and digitally marginalised groups to achieve better health outcomes through the support of others. Drawing on the view of health literacy as shared resources, knowledge, and expertise distributed across individuals’ social networks, the paper argues that, apart from an emphasis on independent mastery of health-related texts and practices by an individual, literacy mediation provides an alternative pathway to enhancing health equity for less-advantaged groups, by mobilising the resources of people who help them with navigating challenging digital health texts.